Impact of Risk Management Committee Characteristics and Institution Size on Credit Riskiness: A Study Based on Pakistani Financial Industry - Ahmad Rizvi, Syed Sami (2016)
Learning from the historical accounts where financial corporations collapsed, failed and lost investor confidence are all in some way or the other linked with the negligence on adopting yet following the codes and guidelines of corporate governance frameworks in true and spirit. Being an essential element of the corporate governance, risk governance has gained importance in the recent years whereby the regulatory bodies and the relevant authorities of the financial sector have laid emphasis on implementation and improvement of risk management framework. Subsequently in order to strengthen the risk governance and management frameworks, the formation of board level sub committees have been encouraged by the regulatory bodies i.e. Securities and Exchange Commission and the Central bank of Pakistan i.e. State Bank of Pakistan. All banking institutions and development financial institutions have employed board level risk committees in order to improve the performance of their companies thereby ultimately safeguarding the interests of investors, one of the objectives of corporate governance. Non-performing loans depicting high level of credit risks have remained a problem for the banking institutions of Pakistan. Since risk committees are actively employed in the institutions, it was intriguing to find the association of the risk committees and its characteristics on the credit riskiness of these firms. Hence the study incorporates a panel data regression based on the secondary data of forty banking institutions operating in Pakistan for a period of five years i.e. 2010 to 2014. Implications of risk committee characteristics including % of directors present in the committee, independence of the committee, number of committee meeting, committee quality, director busyness and institution size were analysed in relation to credit riskiness. Independence of the committee and institution size displayed significant negative associations on credit riskiness indicating that increasing the employment of independent directors in the committees would decrease the credit riskiness of the firms indicating not only better performance in terms of profitability of the firms but also safeguarding the interest of the shareholders. Similarly, the negative relationship between the institution size and credit riskiness further elaborates the notion that bigger sized institutions are less affected by credit risks as they tend to absorb the shocks with regards to credit losses. Moreover growth of the institution amplifies the resources of the institutions whereby they could engage into litigations and make recoveries. The findings of the study further outline implications for the policy makers, regulatory authorities, potential new entrants and existing institution. These could attain benefits of the results and could further assess the risk committees as employed in their respective institutions. Similarly, the policy makers including the Securities and Exchange Commission of Pakistan and the State Bank of Pakistan could lay more emphasis on employment of independent directors while revising and redesigning the corporate governance policies and guidelines.